2012
DOI: 10.1111/j.1467-9922.2012.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Task Complexity, Modality, and Aptitude in Narrative Task Performance

Abstract: The study reported in this paper investigated the relationship between components of aptitude and the fluency, lexical variety, syntactic complexity, and accuracy of performance in two types of written and spoken narrative tasks. We also addressed the question of how narrative performance varies in tasks of different cognitive complexity in the written and spoken modes. Our findings indicate a complex interaction between aptitude components and task performance under different conditions. The components of apt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
90
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 45 publications
17
90
2
3
Order By: Relevance
“…Moreover the complexity of ideas and the use of notes would certainly be influential in making a text less repetitious. This result contrasts with Kormos and Trebits (2012) who found that a more complex narration task resulted in a lower D value than a less complex description task. They argue that there is a cost in more complex tasks which require more attention resources which results in repetition.…”
Section: Task Topic and Lexical Diversitycontrasting
confidence: 56%
See 1 more Smart Citation
“…Moreover the complexity of ideas and the use of notes would certainly be influential in making a text less repetitious. This result contrasts with Kormos and Trebits (2012) who found that a more complex narration task resulted in a lower D value than a less complex description task. They argue that there is a cost in more complex tasks which require more attention resources which results in repetition.…”
Section: Task Topic and Lexical Diversitycontrasting
confidence: 56%
“…In a study of lexical diversity (D) and language aptitude, Kormos and Trebits (2012) found a payoff between lexical diversity and grammatical sensitivity. That is to say, the ability to detect grammatical patterns correlated with greater clause length (p. 459).…”
Section: Heterogeneity In Lexical Diversitymentioning
confidence: 99%
“…He has clearly contended that "progress along the route from novice to expert that instructional sequences of tasks enable is a result of the interaction between the demands that tasks place on learners, and the strengths and weaknesses in abilities that they bring to them" (Robinson, 2015, p. 2). Although the contribution of learner-related variables in developing language competence has been sufficiently investigated in other language skills (e.g., speaking and reading), and even in L1 writing (Dörnyei & Kormos, 2000;Kormos & Trebits, 2012), the link between L2 writing and learner factors is still unexplored. It is expected by Kormos (2012) that individual writers with varying cognitive abilities will show different efficiency levels in managing the complex cognitive and linguistic processes of writing, and in utilizing the beneficial function of writing for L2 development.…”
Section: The Journal Of Asia Teflmentioning
confidence: 99%
“…In addition to task features, learner-related variables such as self-efficacy, working memory capacity, and aptitude are also considered as an integral part of Robinson"s (2001aRobinson"s ( , 2001bRobinson"s ( , 2003Robinson"s ( , 2007bRobinson"s ( , 2011 Triadic Componential Framework. These factors can influence task performance by intervening the way learners attend to different aspects of language, handle attentional limitations, and also acquire particular aspects of linguistic competence (Kormos & Trebits, 2012). Thus, in the current study, we also explored if learners with different levels of language aptitude may benefit from task manipulation in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…These studies consist of effect of extroversion/introversion on language learning strategies (Imanpour, 2005), relation between affective variables and speaking skill (Ashtari, 2002;Do¨rnyei & Kormos, 2000;Kormos & Trebits, 2012), the impact of extroversion/introversion on vocabulary learning (Saemian, 2001), the effect of extroversion/introversion on evaluation of writing (Carrell, 1995), relation between personality and academic performance (Chamorro-Premuzic and Furnham, 2003;Rindermann & Neubauer, 2001;Sanchez-Marin et al, 2001;Pulford and Sohal, 2006), and influence of personality factors on reading skill (Li and Chingell, 2010). In the following lines some of the relevant studies would be discussed in details.…”
Section: Literature Reviewmentioning
confidence: 99%